Promoting Religious Moderation: What Students of Islamic Studies Program Can Do - Faizin, Faizin; Rahmi, Rahmi; Alhafiz, Rasyid (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Higher Education students are considered objects of strengthening religious moderation. At the same time, students have the potential to be involved in mainstreaming religious moderation. This paper aims to show the moderate potential of Islamic students and their role in mainstreaming religious moderation, both in knowledge, reasoning, and awareness of religious moderation. In addition, this study also reveals the role and position of Islamic students as part of the demographic bonus in promoting religious moderation in Indonesia. This research was conducted with a current embedded design, mixing quantitative and qualitative simultaneously. The research data comes from Islamic study program students' responses, which are confirmed through interviews. The results of this study indicate that Islamic study program students have a high potential for knowledge (availability of information and reasoning) and awareness (value system, positive perspective, and behavioral consistency) of religious moderation. Thus, they are identified as fulfilling the criteria of being moderate students. Their role in mainstreaming religious moderation has clear objectives, strategies, and distinctive action patterns. Their potential and role can be maximized as part of the demographic bonus to counteract the flow of radicalism and extremism in their circles